Die definiëring van persoonlike besparing: Die Suid-Afrikaanse situasie 1965.1 tot 1984.4 - P. Styger; J. H.P. Van Heerden (South African Journal of Business Management, 1987)
– The definition of personal savings: The South African situation 1965.1 to 1984.4 The personal savings definition and through that also the time series of personal savings in South Africa in common use, can be described as personal savings as published, amongst others, by the South African Reserve Bank. In the computation of the above time series there are certain deficiencies and the time series has been queried since the sixties. The objective of this study was to undertake an empirical study of the definition of personal savings in South Africa and through that also the time series of personal savings, and possibly to improve on these. It was indicated that the published personal savings cannot be regarded as a good definition of personal savings in South Africa. Various alternative personal savings definitions were studied critically and it was indicated that it would seem that long-term insurance premiums plus pension fund contributions (i.e. contractual personal savings) should constitute the personal savings definition for South Africa.
Keywords: 650